HYDROCARBON SOLVENTS FROM THE RESIN OF UNDERGROUND GASIFICATION OF ANGREN COAL - Qodirova Feruza; No’monova Sohiba; Mo’ydinova Nilufar; Mukhtaraliyeva Mukhtasar (Journal of new century innovations, 2022)
Abstract. The article discusses the technology of coal production, its components, ways of using it as fuel. Mainly information is given on technologies of gasification of coal from Angren coal mine, and information on methods is also given.